VEGETABLE CROPS IN TECHNOLOGY OF FUNCTIONAL DRY BREAKFASTS FOR HOTEL AND RESTAURANT ESTABLISHMENTS - Белинская, Кристина (SWorldJournal, 2020)
Functional foods are becoming increasingly popular. For the activities of any enterprise it is necessary to meet the needs of the consumer. Therefore, both in the food industry and in the hotel and restaurant industry, it is important to provide consumer